Immunomodulatory effects of fruits of Barringtonia racemosa Linn. - Patil, Prabhakar R.; Patil, Mahesh R.; Mane, Abhay; Patil, Sudha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Barringtonia racemosa (B. racemosa) is used medicinally in treatment of diarrhoea, asthma, coughs, jaundice. It is also used as an analgesic and antipyretic. This plant has also significant anti-tumor activity. However, systematic evaluation of its immunomodulatory effects has not been reported. In present study the hydroalcoholic extract of fruits of B. racemosa has been evaluated for its immunomodulatory properties in animal models. Methods: Extract of Fruits of B. racemosa was prepared from fruit powder and methanol by macerations and filtration. Healthy albino Wistar rats of either sex having 110-160 g body weight were used for this study. 1. Delayed type hypersensitivity reaction (DTH) using Sheep red blood cells (SRBCs): After immunization with SRBC effect of cyclophosphamide and hydroalcoholic extract of B. racemosa was seen on paw volume changes in rats challenged with SRBC by using digital Plethysmometer. 2. Humoral antibody response to SRBC: Animas were immunized with SRBC and treated with cyclophosphamide and hydroalcoholic extract of B. racemosa. Serum of these animals was observed for haemagglutination titer. Results: Fruits extract at the dose of 5 mg/kg i.p. showed significant decrease in DTH response as compared to that of control group animals. However, the effect of extract was less potent as compared to that of cyclophosphamide treated group. In haemagglutination titer assay, antibody titer in case naïve control, SRBC treated, cyclophosphamide treated and extract treated groups was 1:1, 1:32, 1:8 and 1:16 respectively. Conclusions: The hydroalcoholic extract of this fruits was found to inhibit SRBCs induced DTH in rats. Similarly, SRBCs induced antibody titer was also reduced.